The Assessment of the impact of sanatorium treatment on patients with hip joint endoprosthesis - Wojtaś, Julian; Szymańska, Justyna (Journal of Education, Health and Sport, 2025)
Background: As the years go by, hip replacement procedures, also known as hip endoprosthesis, are becoming more common. As life expectancy increases, it can be assumed that this number will continue to rise, with some sources reporting that it will increase as much as sevenfold by 2030. Purpose: The purpose of this study is to evaluate the impact of a 21-day sanatorium treatment on physical fitness and quality of life after hip replacement surgery. Methodology: selected measurements and tests were performed on the first and last day of the sanatorium stay. A questionnaire on subjective assessment of quality of life was completed on the first day of stay and one month after the end of the sanatorium by telephone. The tools used were, measurement of range of motion with goniometer, strength with Lovett scale, TUG, NRS and SF-36 Conclusions: The range of motion of flexion and abduction in the hip joint subjected to endoprosthesis increased statistically significantly. The time required to walk a distance of 6 meters in the “Stand Up and Walk” test as well as pain complaints on the NRS scale decreased significantly statistically. There was a favorable statistically significant change in all aspects examined by the SF-36 questionnaire.